A proactive approach: Examples for integrating disaster risk reduction and mental health and psychosocial support programming. (15th February 2021) - Gray, Brandon; Eaton, Julian; Christy, Jayakumar; Duncan, Joshua; Hanna, Fahmy; Kasi, Sekar
Abstract: Natural disasters and humanitarian emergencies exert devastating impacts globally. Among these effects are disruptions in mental health and psychosocial well-being. Traditionally, mental health and psychosocial support (MHPSS) interventions have been implemented in response and recovery phases. Yet, the field of disaster management has demonstrated a shift towards disaster risk reduction (DRR). The degree to which the MHPSS field has followed this trend has been limited by several factors, including a lack of consensus-based guidance for MHPSS and DRR integration. However, examples from the field exist and demonstrate the feasibility of taking proactive approaches to supporting mental health and well-being and building better before emergencies occur. The following article outlines two case examples, one project in Sierra Leone and another in India, integrating MHPSS and DRR approaches and principles. Lessons learned from these cases and specific challenges in each context are highlighted and discussed.